A VARIANT FOR USING REGRESSION ANALYSIS TO ASSESS THE ELECTROMAGNETIC ENVIRONMENT IN AN URBAN AREA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The current study was conducted by making a series of experimental measurements of the electric field strength E.  The obtained results have been interpreted using the method of mathematical modelling because the object of study – electromagnetic environment (EME) is a multifactorial system. With the accepted limitation of considering the influence of only two factors (frequency and time intervals) a two-factor regression analysis was used. The processing of the obtained data was performed by two-dimensional quadratic objective function.